Gao xiao neng wang zhan jian zhi zhi nan = Even faster web sites / = Even faster web sites - Souders, Steve (GoTop Information, Inc., 2013)
Detailed summary in vernacular field.
Includes index
Keywords: Web sites -- Design; Web site development; JavaScript (Computer program language); Asynchronous transfer mode; Sites Web; Conception; Sites Web; Développement; JavaScript (Langage de programmation); Mode de transfert asynchrone; Web sites; Design